Moderate intake of docosahexaenoic acid raises plasma and platelet vitamin E levels in cystic fibrosis patients. (December 2016) - Véricel, Evelyne; Mazur, Stéphane; Colas, Romain; Delaup, Véronique; Calzada, Catherine; Reix, Philippe; Durieu, Isabelle; Lagarde, Michel; Bellon, Gabriel
Abstract: Patients with cystic fibrosis have increased oxidative stress and impaired antioxidant systems. Moderate intake of docosahexaenoic acid (DHA) may favor the lowering of oxidative stress. In this randomized, double-blind, cross-over study, DHA or placebo capsules, were given daily to 10 patients, 5 mg/kg for 2 weeks then 10 mg/kg DHA for the next 2 weeks (or placebo). After 9 weeks of wash-out, patients took placebo or DHA capsules. Biomarkers of lipid peroxidation and vitamin E were measured at baseline, and after 2 and 4 weeks of treatment in each phase. The proportions of DHA increased both in plasma and platelet lipids after DHA supplementations. The lipid peroxidation markers did not significantly decrease, in spite of a trend, after the first and/or the second dose of DHA but plasma and platelet vitamin E amounts increased significantly after DHA supplementation. Our findings reinforce the antioxidant potential of moderate DHA intake in subjects displaying increased oxidative stress. Highlights: Lipid peroxidation has been reported to occur in plasma of cystic fibrosis (CF) patients. Moderate intake of docosahexaenoic acid (DHA) may lower oxidative stress. Plasma and platelet vitamin E increased after moderate intake of DHA in CF patients. Our study supports the antioxidant potential of moderate DHA intake in CF patients.